Risk of SARS-CoV-2 infection in healthcare workers with inflammatory bowel disease: a case-control study - Aurelien Amiot; Anne Bourrier; Jean-Marc Gornet; Olivier Dewit; Stephane Nancey; Romain Altwegg; Vered Abitbol; David Laharie; Catherine Reenaers; Charlotte Gagnière; Anthony Buisson; Maria Nachury; et al. (Elsevier, 2023)
Summary: Background: Whether healthcare workers with inflammatory bowel disease (IBD) are at increased risk of Novel coronavirus disease (COVID-19) due to occupational exposure is unknown. Aim: To assess the risk of COVID-19 in healthcare workers with IBD. Methods: A case control study enrolled 326 healthcare workers with IBD from 17 GETAID centres and matched non-healthcare workers with IBD controls (1:1) for gender, age, disease subtype and year of diagnosis. The study period was year 2020 during the COVID-19 outbreak. Results: In total, 59 COVID-19 were recorded among cases (n = 32) and controls (n = 27), including 2 severe COVID-19 (requiring hospitalization, mechanic ventilation) but no death. No difference was observed between healthcare workers and controls regarding the overall incidence rates of COVID-19 4.9 ± 2.2 vs. 3.8 ± 1.9 per 100 patient-semesters, P = 0.34) and the overall incidence rates of severe COVID-19 (0.6 ± 7.8 vs. 0.3 ± 5.5 per 100 patient-semesters, P = 0.42). In multivariate analysis in the entire study population, COVID-19 was associated with patients with body mass index > 30 kg/m2 (HR = 2.48, 95%CI [1.13-5.44], P = 0.02). Conclusion: Healthcare workers with IBD do not have an increased risk of COVID-19 compared with other patients with IBD.